Asymptotics of the values of approximations in the mean for classes of differentiable functions by using biharmonic Poisson integrals - Kalchuk, I. V.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
Complete asymptotic decompositions are obtained for values of exact upper bounds of approximations of functions from the classes W^r_1,r N, and WJr, W^r_1,r N{1}, by their biharmonic Poisson integrals.